EFFECT OF DIFFERENT PROPAGATION TECHNIQUES AND GAMMA IRRADIATION ON MAJOR STEVIOL GLYCOSIDE’S CONTENT IN STEVIA REBAUDIANA - S. A. Khalil; R. Zamir; N. Ahmad (Journal of Animal and Plant Sciences, 2014)
In this study, the effect of different propagation techniques (in vitro and in vivo) and gamma irradiation has been investigated on Steviosides (Stev) and Rebaudioside (Reb) A content in Stevia rebaudiana Bertoni. Stev and Reb-A are the major active compounds of Stevia rebaudiana that is non-genotoxic and frequently used in many food items as sugar alternative due to its extremely sweet taste. After ingestion these compounds cannot enter into the blood stream and useful for diabetic patients. Seeds and calli were irradiated with different doses of gamma rays and LD50 (8.75 Gy) and GR50 value (13.33 Gy) were calculated on the basis of germination percentage and growth reduction. Higher germination (20%) was observed in 2.5 Gy irradiated seeds as compared to control (23.31%). Plantlets were obtained from both seeds and callus cultures. The leaves from these mutant plants were subjected to High Performance Liquid Chromatography (HPLC) for Stev and Reb-A contents. Stev and Reb-A content were also determined in different in vitro (callus, shoots, plantlets and acclimatized plants) and in vivo (seeds, floral parts, stem parts and roots) grown tissues and organs. Higher Stev content (2.597±1.40 mg/g-DW) was recorded in the leaves of MV1 generation of callus derived plants as compared to control (1.733±0.63 mg/g-DW). Reb-A content was found lower than Stev content. Similarly in vitro shoots showed higher biosynthesis of Stev content (2.808±0.70 mg/g-DW) than other in vitro and in vivo grown tissues and organs. These studies are reported for the first time from Pakistan which can be used for different commercial applications. It is concluded from the current study that in vitro shoots (2.808±0.70 mg/g-DW) obtained through tissue culture serve the best organs for Stev and Reb-A content accumulation than other in vivo and irradiated tissues.
Keywords: Stevia rebaudiana; seeds; callus culture; gamma radiation; HPLC; Steviol Glycosides; Stevioside; Rebaudioside-A